2002
DOI: 10.1002/ana.10094
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment slows disease progression in R6/2 Huntington's disease mice

Abstract: Huntington's disease is a genetic disorder that causes motor dysfunction, personality changes, dementia, and premature death. There is currently no effective therapy. Several transgenic models of Huntington's disease are available, the most widely used of which is the R6/2 mouse, because of its rapid disease progression. Environmental enrichment alters gene expression in the normal mouse brain, and modulates the course of several neurological disorders. Environmentally enriched mice may actually mimic human di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
180
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(190 citation statements)
references
References 34 publications
8
180
0
1
Order By: Relevance
“…However, questions arise regarding the differences in phenotype between the shortstop and the R6͞2 short fragment mouse model. The R6͞2 model expresses the first exon of htt with 144 (17) to 205 (27) polyQ repeats (compared with 120Q in the shortstop) and demonstrates rotarod deficits (28), nonselective brain weight decreases, and an early death phenotype (17). It is surprising that shortstop and R6͞2 mice share no phenotypic features.…”
Section: Discussionmentioning
confidence: 99%
“…However, questions arise regarding the differences in phenotype between the shortstop and the R6͞2 short fragment mouse model. The R6͞2 model expresses the first exon of htt with 144 (17) to 205 (27) polyQ repeats (compared with 120Q in the shortstop) and demonstrates rotarod deficits (28), nonselective brain weight decreases, and an early death phenotype (17). It is surprising that shortstop and R6͞2 mice share no phenotypic features.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is not known whether expression of the GH transgene used in these studies is modified by environmental conditions. For transgenic mice strains, environmental enrichment can provide morphological compensation in the brain for the effects caused by a transgene (44)(45)(46). In general, environmental complexity reduces hormonal effects on behavior (47), and GH treatment of nontransgenic brown trout (Salmo trutta) had stronger phenotypic effects in the hatchery than under natural conditions (48).…”
Section: Discussionmentioning
confidence: 99%
“…Two independent groups have analyzed the effect of an increased environmental stimulation on the phenotype and neuropathology of R6 mice van Dellen et al, 2000;Hockly et al, 2002;Glass et al, 2004;Spires et al, 2004). These studies have demonstrated that the exposure of R6/1 (van Dellen et al, 2000;Glass et al, 2004;Spires et al, 2004) or R6/2 (Hockly et al, 2002) mice to an enriched environment (consisting of large standard cages with cardboard, paper and plastic objects, which were changed every two to three times per week) delayed the onset of motor symptoms, decreased the severity of the clasping phenotype, and reduced the loss of the peristriatal cerebral volume. Carter et al (2000) also demonstrated that, improving the access to food and water had beneficial effects.…”
Section: Environmental Enrichmentmentioning
confidence: 99%